Approximate arithmetic circuits - Navabharath Reddy G; Sruti Setlam; V. Prakasam; D. Kiran Kumar (International Journal of Reconfigurable and Embedded Systems (IJRES), 2020)
Low power consumption is the necessity for the integrated circuit design in CMOS technology of nanometerscale. Recent research proves that to achieve low power dissipation, implementation of approximate designs is the best design when compared to accurate designs. In most of the multimedia applications, DSP blocks has been used as the core blocks. Most of the video and image processing algorithms implemented by these DSP blocks, where result will be in the form of image or video for human observing. As human sense of observation is less, the output of the DSP blocks allows being numerically approximate instead of being accurate. The concession on numerical exactness allows proposing approximate analysis. In this project approximate adders, approximate compressors and multipliers are proposed. Two approximate adders namely PA1 and PA2 are proposed which are of type TGA which provides better results like PA1 comprises of 14 transistors and 2 error distance, achieves reduction in delay by 64.9 % and reduction in power by 74.33% whereas the TGA1 had 16 transistors and more power dissipation.PA2 comprises of 20 transistors and 2 error distance. Similarly PA2 achieves delay reduction by 51.43%, power gets reduced by 67.2%. PDP is reduced by 61.97 % whereas TGA2 had 22 transistors. An Approximate 4-2 compressor was proposed in this project to reduce the number of partial product. The compressor design in circuit level took 30 transistors with 4 errors out of 16 combinations whereas existing compressor design 1 took 38 and design 2 took 36 transistors. By using the proposed adder and compressors, approximate 4x4 multiplier is proposed. The proposed multiplier achieves delay 124.56 (ns) and power 29.332 (uW) which is reduced by 68.01% in terms of delay and 95.97 % in terms of power when compared to accurate multiplier.